Penanganan Korupsi Di Dunia Birokrat: Sebuah Perspektif Relatifisme Kultural yang Strukturalis - Aunalal Zany Irayati (Business Administration Department - Universitas Katolik Parahyangan, 2008)
The problem of corruptions in Indonesia bureaucrats are not the new problems. Fromlong time ago, this conditions still a live and tend to be a culture. This article conductedto make the opinion about problem solving from the corruptions in Indonesiabureaucrats. The opinion and problem solving in this article are focused fromthe cultural relativism perspectives. They would always begun from the individualtransactional and make everybody in organization is somebody special.Keywords: Corruptions, Indonesia Bureaucrats, Cultural Relativism Perspectives